Enraizamento social nos circuitos de proximidade de produtos agroecológicos - Fagundes, Rodrigo Mello (2017)
This work discloses embeddedness, as rooting or imersion from social relationships involving farmers, concerning commercialization circuits for agroecological products, built from proximity links. The main object of the work is to identify modes of embeddedness and their relationship with the structural immersion itself, through which farmers assume a stronger relationship with the organization of the routes, or the way how they prioritize, access and incorporate themselves to commercialization routes, and in organic or agroecological agriculture. The research has been performed by means of interviews made with semi-structured scripts, adapted for each case. Data as collected had their content analyzed by placing them into context in sense cores. As a result, we have identified the importance of social relationships for the formation of a base for agroecological agriculture, also in the access and establishment of commercialization routes or, in some cases, the immersion of enterprises in farmers’ networks. Furthermore, taking each case as a reference, we could identify different values and motivations, or characterize embeddedness from virtues as highlighted in the relationships, such as links and relations for solidarity, cooperation, partnerships, contribution, responsibilities, access and spread of information, etc. Consequently, we concluded that social relationships are a key for the immersion in proximity routes between farmers, and also involving organizations. We consider that institutions emerge among relationships and define given standards such as agreements and functions by incorporating farmers to the routes, and that the immersion of farmers in social/technical networks, involving different organizations and other social circles, may improve the knowledge and spread of more complex and diversified cultivation systems and methods.